Insult To The Government: Legal And Maqa̅sid Al-Syari̅'ah Analysis Of Freedom Of Expression - Firdaus, Royan Ahila; Ridho, Muhammad Rosyid; Rahayu, Fadilah Qotimatun Puji (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
Since the enactment of Law Number 1 of 2023 concerning the Criminal Code, a main problem related to Articles 240-241 regarding insults to the government has arisen. This has the potential to criminalize public freedoms. This study examines these provisions through the lens of maqāṣid al-sharī'a, which was chosen as the framework of analysis due to its ability to provide a benefit-based philosophical framework that is considered more appropriate than the textual approach of positive law. The method used is normative legal research. The results of the study indicate that Articles 240-241 are subject to multiple interpretations and overlap with Article 433 regarding defamation of individuals. In answering this problem, maqāṣid al-sharī'a provides a profound solution with a balancing principle. Freedom of opinion, as part of ḥifẓ al-'aql (safeguarding reason), is required to be in harmony with ḥifẓ an-nafs wa al-'ird (safeguarding the soul and honor). Therefore, this approach is expected to provide a basis for protecting freedom of expression more fairly, allowing freedom of expression to be protected while upholding respect for the state, while still weighing the benefits and harms of criticism substantively.